2012
DOI: 10.1164/rccm.201107-1203oc
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of 634 HIV-Negative Patients with Mycobacterium avium Complex Lung Disease

Abstract: The first-line treatment regimen was not associated with all-cause mortality. FC or FC+NB disease, BMI less than 18.5 kg/m(2), and anemia were negative prognostic factors for both all-cause and MAC-specific mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
240
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(264 citation statements)
references
References 37 publications
18
240
5
1
Order By: Relevance
“…The 1-year mortality rate in our study (9%) was lower than that (25%) found in a previous study of macrolide-resistant MAC-LD (14), although the 5-year mortality rate was significantly higher (47%) in the present study. Moreover, the 5-year mortality rate in patients with macrolide-resistant MAC-LD in our study was much higher than those (13 to 26%) in patients with newly diagnosed MAC-LD in previous studies (35)(36)(37). These time-dependent increases in mortality indicate the difficulty of managing patients with macrolide-resistant MAC-LD.…”
Section: Discussioncontrasting
confidence: 70%
“…The 1-year mortality rate in our study (9%) was lower than that (25%) found in a previous study of macrolide-resistant MAC-LD (14), although the 5-year mortality rate was significantly higher (47%) in the present study. Moreover, the 5-year mortality rate in patients with macrolide-resistant MAC-LD in our study was much higher than those (13 to 26%) in patients with newly diagnosed MAC-LD in previous studies (35)(36)(37). These time-dependent increases in mortality indicate the difficulty of managing patients with macrolide-resistant MAC-LD.…”
Section: Discussioncontrasting
confidence: 70%
“…Radiographic abnormalities were classified according to distinct disease patterns on chest computed tomography (CT) as (i) fibrocavitary, (ii) nodular bronchiectatic, and (iii) unclassifiable forms (8). Patients were diagnosed with the fibrocavitary form if CT showed the presence of apical fibrocavitary lesions, and they were diagnosed with the nodular bronchiectatic form if CT showed multiple nodules with bronchiectasis.…”
Section: Methodsmentioning
confidence: 99%
“…Hazard ratio (HR) and Cox regression analysis were used to calculate the adjusted risk. Independent variables were selected on the basis of (i) their statistical significance in univariate analysis and (ii) clinical significance revealed in previous studies (4,8,10). All tests of significance were twosided; P values of Ͻ0.05 were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Additional negative prognostic indicators were BMI , 18.5 kg/m 2 , anemia, and elevated C-reactive protein level. 39 Th e signifi cance of more than one mycobacterial species in the same patient has been uncertain. A recent report considered 53 patients encountered over a 12-year period who received treatment for MAC PNTM and had M abscessus subspecies abscessus ( Maa ) isolated during therapy.…”
Section: Recent Insightsmentioning
confidence: 99%